Alfonsine Astronomy - Kremer, Richard L. (ED); Husson, Matthieu (ED); Chabás, José (ED) (Brepols Publishers, 2022)
Compiled between 1262 and 1272 in Toledo under the patronage of Alfonso X, the Castilian Alfonsine Tables were recast in Paris in the 1320s, resulting in what we now call the Parisian Alfonsine Tables. These materials circulated widely and fostered astronomical activities throughout Europe. This resulted in a significant number of new works, of which there are a few hundred, extant in more than 600 manuscript codices and dozens of printed editions. These manuscripts and imprints, broadly contemporary to the works they witness, comprise the written record of Alfonsine astronomy and provide the focus of this volume. A first series of essays examines individual manuscripts containing Alfonsine works. The authors seek to reconstruct, from the manuscript evidence, the cultural, astronomical and mathematical worlds in which the manuscripts were initially copied, compiled, used and collected. A second series of essays turns from the particular codex to the individual work or author. These contributions ask how particular works have been transmitted in surviving manuscript witnesses and how broader manuscript cultures shaped the diffusion, over two centuries, of Alfonsine astronomy across Europe. A final essay reflects on the challenges and opportunities offered by digital humanities approaches in such collective studies of a large manuscript corpus.